2023
DOI: 10.3390/jcm12082937
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Multidimensional Assessment of Interoceptive Awareness (MAIA) Questionnaire in Colombian University Students

Abstract: Introduction: The university student population is influenced by multiple factors that affect body awareness. Identifying the body awareness status of students is crucial in creating self-care and emotion management programs to prevent diseases and promote health. The Multidimensional Assessment of Interoceptive Awareness (MAIA) questionnaire evaluates interoceptive body awareness in eight dimensions through 32 questions. It is one of the few tools that enable a comprehensive assessment of interoceptive body a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This study was conducted using MAIA-2 tool to assess the level of interoceptive awareness among the study participants, where MAIA tool holds significant advantages that allow more differentiated assessment of essential psychological aspects of the perception and evaluation of body sensations [ 3 ]. Furthermore, MAIA is considered as one of the few tools that enable a comprehensive assessment of interoceptive body awareness by involving multiple dimensions of analysis [ 34 ]. Indeed, the MAIA comprises eight scales that encompass five key dimensions of body awareness, where these scales provide a comprehensive understanding of different aspects of body awareness through eight subscales including “Noticing”, which involves being aware of body sensations, and “Not-Distracting” and “Not-Worrying”, which relate to emotional reactions and attentional responses to sensations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted using MAIA-2 tool to assess the level of interoceptive awareness among the study participants, where MAIA tool holds significant advantages that allow more differentiated assessment of essential psychological aspects of the perception and evaluation of body sensations [ 3 ]. Furthermore, MAIA is considered as one of the few tools that enable a comprehensive assessment of interoceptive body awareness by involving multiple dimensions of analysis [ 34 ]. Indeed, the MAIA comprises eight scales that encompass five key dimensions of body awareness, where these scales provide a comprehensive understanding of different aspects of body awareness through eight subscales including “Noticing”, which involves being aware of body sensations, and “Not-Distracting” and “Not-Worrying”, which relate to emotional reactions and attentional responses to sensations.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous research in Iran [35], Korea [36], Japan [37], Colombia [34], and Turkey [38] examined the MAIA reliability and validation to be used and applied among different study populations. This tool was validated to suit populations with different languages, and also to suit different sociocultural groups, where these validations allow clinicians and researchers to use MAIA among these populations [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Valenzuela-Moguillansky et al 52 removed two items (4 and 8), while Cali et al 38 excluded five items (4, 7, 10, 12, and 19) from MAIA to improve the 8-factor structure. A 7-factor solution of EFA was found in several studies 46 , 47 , 50 . In the Portuguese sample, Machorrinho et al 46 showed a 7-factor solution in EFA (without Body Listening scale).…”
Section: Introductionmentioning
confidence: 86%
“…In the Portuguese sample, Machorrinho et al 46 showed a 7-factor solution in EFA (without Body Listening scale). Similarly, Montoya-Hurtado 47 showed a 7-factor structure by removing the Not Worrying scale and item 6 of the MAIA. Teng et al 50 removed six items, and the Noticing scale and good fit indices were achieved by modification (residual correlations between some items).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation